Lignite oxidative desulphurization - Volodymyr Gunka; Serhiy Pyshyev (International Journal of Coal Science & Technology, 2014)
Abstract The process of lignite desulphurization via its treatment by an oxidant (air or air–steam mixture) has been studied. The research objective was useful determination of steam application in oxidative lignite desulphurization. It has been proved that the water steam should be included in the oxidant composition to increase the hydrogen sulphide and combustible constituent content in the gases obtained during the processes under research. The impact of factors which affect the reactions between solid (in our case – lignite) and gaseous reagent (oxidant, i.e. air and or air–steam mixture) upon the research process has been investigated, if these reactions occur in the kinetic area. Such factors are linear rate of oxidant movement and coal grain size. The values of oxidant movement linear rate and coal grain size, which the reaction transfer from pyrite sulphur and organic content of lignite from diffusion into kinetic area occurs by, have been determined. Under these “transfer” conditions, the values of coefficients of oxidant mass transfer (β, m/s) as well as Sherwood criteria and boiling layer differences have been calculated.